Beaverlodge uranium mine closure – balancing current expectations with past practices - Webster, M (Mine Closure 2011: Proceedings of the Sixth International Conference on Mine Closure, 2011)
The former Beaverlodge uranium mining and milling properties are located in the northwest corner of Saskatchewan, Canada and were operated by Eldorado Mining & Refining Ltd., a former federal crown corporation, between 1952 and 1982. Decommissioning and reclamation of the Beaverlodge properties was completed in 1985. With the establishment of closure end-point objectives agreed to by both the federal and provincial regulatory agencies, the properties entered a period of transition phase monitoring, originally envisioned to last ten years. However, with no formal exit agreement or strategy in place, transition phase monitoring has continued to this day. In 2007 the province of Saskatchewan brought forth an innovative approach to the long-term management of decommissioned industrial properties. The province’s institutional control program provides industry with clear direction and expectations that once they meet their obligations for decommissioning there will be a responsible authority to accept custodial responsibility of the property in perpetuity. Some of the Beaverlodge properties have recently been transferred to institutional control, while the rest remain in the transition phase. Cameco Corporation, responsible for the management of the properties on behalf of the Canadian government, has collaborated with the regulatory agencies and stakeholders to develop a management framework to guide the assessment and decision-making process regarding potential additional remedial activities for the Beaverlodge properties. The management framework seeks to balance current decommissioning expectations with the presence of legacy issues and past close-out agreements, ultimately relying on benefit-cost evaluation to arrive at final criterion that is acceptable to the majority of the relevant stakeholders. By working through the management framework process, the remaining Beaverlodge properties should eventually meet decommissioning expectations and be allowed to transfer to institutional control.